Synthetic drug production in Belgium: Environmental harms as collateral damage? - Mafalda Pardal; Charlotte Colman; Tim Surmont (Journal of Illicit Economies and Development (JIED), 2021)
The production of illicit drugs contributes to important environmental harms. In the European context, the production of synthetic drugs, particularly MDMA and amphetamine (and more recently methamphetamine), increasingly poses environmental challenges. The production of these substances in Europe is mainly concentrated in the Netherlands and to a lesser extent in Belgium. In this contribution we focus on the Belgian case, particularly in Flanders-the Belgian region where synthetic drug production has been more present. The goals of our analysis are 1) to document the presence of illicit synthetic drug production and dumping of chemical waste material in that region, 2) to explore the media coverage of environmental harms associated with those activities, and 3) to identify the range of reported environmental harms. We draw on data from the Belgian Federal Police and on an analysis of 289 news articles published in selected Flemish newspapers (2013-2020). The findings indicate that although there is an increasing trend in the presence of synthetic drug production and dumping sites in Belgium, the details on the nature and extent of environmental harms are often unknown. Besides difficulties around detecting certain types of dumping events, there are also important blind spots in terms of the monitoring of environmental hazards by law enforcement agencies and how that information is shared among the relevant actors.
Keywords: 330; Belgium; dumping; environmental harms; production; synthetic drugs; waste